EFEKTIVITAS KERJASAMA INDOMALPHI TERHADAP KEAMANAN DI BIDANG KEMARITIMAN INDONESIA - Andre Bob Rinaldi Sitompul; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The high incidence of crime and piracy in the Sulu-Sulawesi Sea has an impact not only on bordering countries but also for user countries that use this route as cargo ship traffic. Indonesia, Malaysia, and the Philippines responded to this security threat by establishing security cooperation in the form of the Indomalphi Trilateral security cooperation. For this reason, this study describes how Indomalphi security cooperation can reduce security threats in the Sulu-Sulawesi Sea. This study uses a neorealism perspective developed by Kenneth Waltz, where the main national interest is security and justifies cooperation in the formation of joint securities. The author uses the level of analysis of the nation-state, namely, the behavior of the nation-state as a unified whole as the dominant actor in international relations. The author uses the theory of regime effectiveness proposed by Arild Underdall in explaining the effectiveness of the regime that underlies the formation of cooperation security. To describe this collaboration, the authors collect data from books, journals, websites, dictionaries, Ministry of Defense reports, and ReCAAP on maritime security cooperation. Then processed and analyzed to answer this research question. The results show that the cooperation between Indonesia, Malaysia, and the Philippines has given good results for each country, such as decreasing the rate of ship piracy, illegal fishing, and smuggling of illegal goods as well as making it easier to resolve the kidnapping of Indonesian hostages at the Sulu Sulawesi Sea border in 2016-2019. Keywords: Trilateral Cooperation, Security, Sulu Sea, Ship Piracy